New Provisions in The Sale of State Property (Critical Comparative Analysis Study) - Ibrahim Omer Ibrahim (QALAAI ZANIST JOURNAL, 2020)
This study covered the new provisions in the Law of Selling and Renting State property No. (21) for the year (2013) amending in Iraq and not in force in the Kurdistan Region regarding the sale of state property, The researcher penetrated these provisions and compared them with the provisions contained in the Law of Selling and Renting State property No. (32) for the year (1986), The aim of this is to elicit and extract the right judgments in them regarding the sale of the movable and immovable state property. This study is not limited to presenting the developments mentioned in the applicable law, Rather, the researcher analyzed and evaluated the developments contained in him from his point of view, whether with or without their support, and reinforced this with the reasons that the researcher sees. At the conclusion of the study, the researcher reached a set of conclusions that determined the existence of new provisions, first with support, and with the existence of some provisions, another worthier of amendment, in addition to the presence of some gaps mentioned in the applicable law that the legislator must fill in according to what the researcher suggests through this research.